Molecular Characterization of Intestinal Microflora of Middle-distance Racers in Response to Exercise Stress - Chen, J.; Zhao, L. P.; Qiao, D. C. (The Hong Kong Journal of Sports Medicine and Sports, 2002)
In order to understand the relationship between exercise stress and dynamics of intestinal microflora, three long-runners were selected as our research subjects. ERIC-PCR and community structural probes were used to monitor changes of microbial community structures in these sportsmen's fecal samples on a daily basis for one week. Firstly ERIC-PCR technology was applied to fingerprint the total genomic DNA isolated directly from fresh fecal samples. Then all of ERIC-PCR amplicons from AH1's fecal sample was labeled as mixed probes because his profile was the most complex and thus information intensive. We analyzed the differences among these athletes's intestinal microflora through Southern-blotting. Significant differences among different individuals were observed in the fingerprints of intestinal microflora. Shifts of microbial community structures were observed in the same individual as exercise stress changed over time. It was concluded that ERIC-PCR and Southern blotting may be used as molecular tools for understanding relationship between exercise stress and structural changes of intestinal microflora. Gastrointestinal (GI) problems are common among athletes. Exercise-related symptoms in the upper GI tract can include nausea, bloating, heartburn, and acid reflux; symptoms of the lower GI tract may include diarrhea, the urge to defecate, and rectal bleeding (Green, 1993). A recent study (Worme et al., 1990) of GI complaints in recreational triathletes found that half reported upper GI symptoms like bloating and gas, and 27% had tested positive for occult stool blood. A survey (Green, 1993) of 700 runners revealed that 42% had occasional upper GI symptoms and that these occurred more often during and after hard runs than during and after easy runs. And in another survey (Worobetz et al., 1985) 58% of endurance athletes reported upper GI symptoms, and 61% reported lower GI symptoms. Many factors are believed to play a role. In these factors, dynamics of intestinal microflora is regarded as an important factor which results in the Gastrointestinal (GI) problems. The human gastrointestinal tract harbors a diverse community of microorganisms which include a large number of mainly anaerobic bacteria. These have largely been studied by plate count analysis of fecal samples, which usually contain 1010 to 1011 CFU per g. (Finegold et al., 1983; Savage, 1997). But one of the limitations in using conventional microbiological methods is that only easily cultivable organisms are counted. Bacteria which have obligate interactions with the host or other microorganisms, or which require unknown growth conditions, will not be selected this way. Estimates of culturability of bacteria in the gastrointestinal tract vary from 10 to 50% (Langendijk et al., 1995; Wilson et al., 1996). Other limitations of cultivation include the selectivity of the medium used, the stress imposed by cultivation procedures, and the necessity of strictly anoxic conditions. As a consequence, insight into the interaction between the host and the microbial community, and into the influence of environmental factors on microbial composition, is still lacking. Fortunately, this decade has shown an explosive development in the application of molecular techniques based on nucleic acids to the study of microbial diversity in ecosystems. Many scientists have used rRNA, TGGE (or DGGE) and PCR-based genomic fingerprinting methods including the amplified ribosomal DNA restriction analysis (ARDRA), the random amplified polymorphic DNA (RAPD-PCR) approaches to monitor the structures of different microbial communities without isolation of the component microorganisms (Erwin et al., 1998; Kazuya et al., 1998; Andras et al., 1998; Holger et al., 1999). Although these studies report significant information on specific bacteria and specific individuals, the approaches are time-consuming, expensive, and unsuitable for characterizing complex microbial communities. Recent studies have demonstrated that repetitive element PCR (REP-PCR) is a method which generates DNA fingerprints that discriminate between bacterial species and strains. This method involves the application of oligonucleotide primers based on families of short, highly conserved extragenic repetitive sequences, including the repetitive extragenic palindromes (REP) and the enterobacterial repetitive intergenic consensus (ERIC) sequences. ERIC sequences are repetitive elements of 126 bp and appear to be restricted to transcribed regions of the chromosome, either in intergenic regions of polycistronic operons or in untranslated regions upstream or downstream of open reading frames. Their positions in the genome seem to be different in different species (de Burijin et al., 1992). Because the unique locations of ERIC elements in bacterial genomes allows discrimination at genus, species, and strain levels based on the electrophoretic pattern of amplification products. Many scientists regard it as a simple and reliable method for fingerprinting diverse types of DNA samples which come from the different kinds of bacteria. In this study, ERIC-PCR and mixed probe hybridization technology were developed to describe the bacterial diversity in athletes' fecal samples and to investigate to what extent this diversity can be changed by exercise stress. Firstly we directly extracted the total mixed genomic DNA of the microbial communities in human fecal samples, and then ERIC-PCR was used to compare the difference among different exercise stress in one individual. Finally we labeled AH1's ERIC-PCR products as mixed probe to hybridize with other athlete's banding patterns on sequences level.